2020
DOI: 10.1093/infdis/jiaa377
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials of Broadly Neutralizing Monoclonal Antibodies for Human Immunodeficiency Virus Prevention: A Review

Abstract: Passive immunisation with broadly neutralizing antibodies (bnAbs) is a promising approach to reduce the 1.7 million annual HIV infections globally. Early studies on bnAbs showed safety in humans, but short elimination half-lives and low potency and breadth. Since 2010, several new highly potent bnAbs have been assessed in clinical trials alone or in combination for HIV prevention. Published data indicate that these bnAbs are safe and have a half-life ranging from 15 to 71 days. Only intravenous VRC01 has advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 46 publications
0
69
0
Order By: Relevance
“…This unique study design revealed that while infant T/Fs are more likely to be escape variants from maternal neutralization responses when compared with the non-transmitted maternal variants, the mother’s natural ability to neutralize her own circulating viruses does not define a mother’s MTCT risk. Concerningly, we identified that maternal transmission status was tied to Env amino acid signatures that confer resistance to bnAbs, including those being used in clinical trials for HIV-1 prevention and therapy [66, 67] (https://clinicaltrials.gov/ct2/show/NCT03571204). These results caution the use of passive or active vaccine strategies targeting plasma bnAb activity in pregnant women and indicate that more work will need to address the risks of bnAb escape variants that are fit for virus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…This unique study design revealed that while infant T/Fs are more likely to be escape variants from maternal neutralization responses when compared with the non-transmitted maternal variants, the mother’s natural ability to neutralize her own circulating viruses does not define a mother’s MTCT risk. Concerningly, we identified that maternal transmission status was tied to Env amino acid signatures that confer resistance to bnAbs, including those being used in clinical trials for HIV-1 prevention and therapy [66, 67] (https://clinicaltrials.gov/ct2/show/NCT03571204). These results caution the use of passive or active vaccine strategies targeting plasma bnAb activity in pregnant women and indicate that more work will need to address the risks of bnAb escape variants that are fit for virus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Convalescent plasma with high concentrations of virus-specific immunoglobulins or recombinant fully human antibodies were shown to decrease the viral loads and reduce the mortality in patients infected with the Middle East Respiratory Syndrome Coronavirus (MERS-CoV) 8 , human immunodeficiency virus (HIV) 9 , Ebola virus (EBOV) 10 , and most recently SARS-CoV-2 11 , confirming the efficacy of nAbs as prophylactic and therapeutic agents against viral infection. To date, most of the SARS-CoV-2 nAbs identified were derived from peripheral blood mononuclear cells (PBMC)s of convalescent COVID-19 patients 12 , 13 , or transgenic mice 14 in the context of single B-cell sorting 12 , 14 .…”
Section: Introductionmentioning
confidence: 92%
“…The discovery of broadly neutralising antibodies (bNAbs) in a small group of patients, so-called ‘elite controllers’ [ 17 , 18 ], took the prospect of using mAbs against HIV a major step closer. Several anti-HIV bNAbs are currently in clinical trials [ 19 ]. Current bNAbs are significantly more potent than the early neutralising mAbs.…”
Section: Introductionmentioning
confidence: 99%